Using Mixed Methods in the Evaluation of Online Discussions - Mehanna, Wassila Naamani (Proceedings of the International Conference on Networked Learning, 2006)
This paper is part of a recent empirical enquiry that observed 2000 postgraduate students within various disciplines in four different UK universities and analysed 6 millions words of online discussions. It managed to connect e-learning to students’ learning outcomes and presented a pedagogical model for effective online teaching and learning. This model was validated theoretically and meta-analytically. Moreover, it provided the field with the rationale and the processes for mixing qualitative and quantitative methods for analyzing online discussions. Goodyear (2001) noted: "Analyzing the content of networked learning discussions is a troublesome research area and several commentators have remarked on the difficulty of connecting online texts to discourse to learning" (Page 62). This lack of content analysis of online discussions is due to the time required to perform such analyses and researchers still lack a reliable instrument to analyse the online discussions (Hara, Bonk and Angeli, 2000). Henri (1992) also argued that "research in computer conferencing content is usually restricted to the gathering of quantitative data on participation" (page 122), consequently, leading to possible misinterpretation of the phenomenon. This paper places the emphasis on the devised methodology and provides evidence for pulling the two poles, inductive and deductive approaches, in an unorthodox marriage. This vital process was not possible without mixing the two paradigms within one study and facilitated empirical rigour, interpretation fidelity, and provided the researcher with strong means for inference quality and plausible generalizations that are mostly needed in the emerging field of e-learning (Mehanna, 2004).